Selected issues on theory and methodology of the underground press - Wanda Krystyna Roman (Knygotyra)
The main role of the press, published at any time, is to deliver information and form public opinion. The expectations are even higher regarding the underground press. The history of Poland has numerous references to the theory and methodology of the underground press. It starts from Polish uprisings at the end of the 18th century, goes through the occupation of Polish territories during World War I, includes illegal publications printed between the two World Wars, the underground press circulated during World War II, and ends with the underground press published in the People's Republic of Poland (PRL). Because of the amount of underground press, comprising around 70% of total published press, one can try to look for generalizations regarding the role of the underground press, its place, and the aims it had on Polish soil over the last 200 years.